2005
DOI: 10.5187/jast.2005.47.4.647
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Addition of Rosemary and Citron Peel Powder on POV, TBARS, Microorganisms and Nitrite Scavenging of Emulsion-type Sausages

Abstract: This study was carried out to investigate the effects of addition of 0.1% rosemary, 0.9% citron peel powder and 0.1% rosemary combination with 0.9% citron peel powder on the POV, TBARS, aerobic microorganisms and nitrite scavenging of emulsion-type sausages. The POV values of sausage containing citron peel powder were significantly lower than those of control at 60 days of storage. The TBARS values of sausage containing rosemary, citron peel powder and rosemary combination with citron peel powder were lower th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…Several studies have reported that herbal and plant resources can inhibit lipid oxidation and lead to quality improvement of meat products, including rosemary and citron peel powder (Lee et al, 2005), green tea extract (Yang et al, 2006), Bokbunja ( Rubus coreanus ) extract (Park and Chin, 2007), and medicinal herb extract mix (Choe et al, 2008). Herbal resources have also been applied to substitute nitrite, inhibit the generation of nitrosamines, and reduce artificial antioxidants (Ha et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have reported that herbal and plant resources can inhibit lipid oxidation and lead to quality improvement of meat products, including rosemary and citron peel powder (Lee et al, 2005), green tea extract (Yang et al, 2006), Bokbunja ( Rubus coreanus ) extract (Park and Chin, 2007), and medicinal herb extract mix (Choe et al, 2008). Herbal resources have also been applied to substitute nitrite, inhibit the generation of nitrosamines, and reduce artificial antioxidants (Ha et al, 2001).…”
Section: Introductionmentioning
confidence: 99%